Effectiveness Of Project-Based Learning (PjBL) On Students' Critical Thinking Skills In History Learning - Octavian Hendra Priyatno; Anisa Pitriani; Heri Susanto; Dewica Fatma Nadilla; Fathurrahman Fathurrahman (Jurnal Studi Guru dan Pembelajaran, 2026)
Critical thinking is a key 21st-century skill that is important to develop in the learning process, including in history lessons. However, history teaching practices in schools are still dominated by conventional teacher-centered methods, limiting opportunities for students to hone their critical thinking skills. This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model in improving the critical thinking skills of 11th grade students at SMA Negeri 1 Alalak. This study uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The sample consisted of 62 students, namely class XI-2 as the experimental group and XI-5 as the control group, which were determined through purposive sampling techniques. The research instrument was an essay test based on Anderson and Krathwohl's (2001) critical thinking indicators. Data were obtained through pretest and posttest, then analyzed using descriptive statistics, normality test, homogeneity test, paired sample t-test, and independent sample t-test with the help of SPSS 27. The results showed that both groups experienced an increase, with a greater increase in the experimental group (M = 6.94; d = 0.87) compared to the control group (M = 4.19; d = 0.41). The independent sample t-test showed the effectiveness of PjBL on critical thinking skills (p = 0.004). Although the effect size was moderate, PjBL indicated superiority in strengthening critical thinking skills. However, its effectiveness was influenced by the learning context, student motivation, and school support.